2003
DOI: 10.1001/archinte.163.14.1705
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Warfarin Use Among Ohio Medicaid Patients With New-Onset Nonvalvular Atrial Fibrillation

Abstract: Few in this cohort of Ohio Medicaid patients with incident AF filled prescriptions for warfarin within 30 days of the diagnosis. Several factors, including alcohol or other drug abuse or dependence, psychiatric disease, homelessness or inadequate housing, and lack of a caregiver, were highly prevalent and seemed to bias against warfarin prescribing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 32 publications
0
56
1
1
Order By: Relevance
“…Data on the association between cardiovascular diseases as congestive heart failure and ischemic heart disease with Coumadin compliance was demonstrated in various studies and supports these findings. It is assumed that having increased risk of stroke due to other cardiovascular morbidities increases both patient and care-giver focus on stroke prevention with anti-coagulation treatment (Johnston et al, 2003). Although we did not observe significant differences between compliant and noncompliant patients regarding hospitalisation days, in Phase 2 of the study non-compliant patients were hospitalised almost twice as long (at average) as were compliant patients, and they used the health care services approximately twice as much as compliant patients.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Data on the association between cardiovascular diseases as congestive heart failure and ischemic heart disease with Coumadin compliance was demonstrated in various studies and supports these findings. It is assumed that having increased risk of stroke due to other cardiovascular morbidities increases both patient and care-giver focus on stroke prevention with anti-coagulation treatment (Johnston et al, 2003). Although we did not observe significant differences between compliant and noncompliant patients regarding hospitalisation days, in Phase 2 of the study non-compliant patients were hospitalised almost twice as long (at average) as were compliant patients, and they used the health care services approximately twice as much as compliant patients.…”
Section: Discussioncontrasting
confidence: 63%
“…The reason for that difference might be because younger AF patients do not receive Coumadin as commonly as older patients. Older age (³85 years), as well as younger age (<55 years) decrease the use of warfarin (Johnston et al, 2003). Therefore, the association between age and Coumadin is nonlinear.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study of cardiac arrest in anesthesia used the same institutional databases [25]. For quality-assurance and regulatory purposes, institutional databases are necessary, and studies using institutional databases have now come of age [26,27].…”
Section: Study Limitationsmentioning
confidence: 99%
“…The available data derive from the experiences on patients using VKAs. Various studies have shown that adherence to therapy with VKAs were affected by ethnical origin, economic status, educational level, employment status, missing doses, lack of knowledge on drug usage, use of additional drugs, drug and alcohol dependence, and emotional factors [23][24][25][26]. IN-RANGE study investigated factors affecting adherence to therapy with VKAs for the duration of 32 months.…”
Section: Causes Of Non-adherencementioning
confidence: 99%